Alasan-Alasan Pembatalan Merek Terdaftar Menurut Undang-Undang No.20 Tahun 2016 Tentang Merek dan Indikasi Geografis (Studi Kasus Nomor 45/Pdt.Sus-Merek/2022/PN.Niaga.Jkt.Pst.) - Aslam, Ananda; Mulya, Musa Alam (HUMANIORUM, 2025)
This research examines the reasons for canceling registered trademarks according to Law No. 20 of 2016 concerning Trademarks and Geographical Indications, using case Number 45/Pdt.Sus-Merek/2022/PN.Niaga.Jkt.Pst. as the focus of study. The research aims to analyze the legal basis and judicial considerations behind the trademark cancellation and assess the application of Law No. 20 of 2016 in the case. A normative-juridical approach was employed by analyzing secondary data such as legislation, court decisions, and scholarly literature. The findings reveal that the cancellation is grounded in the violation of essential provisions of the law, specifically those concerning bad faith registration and similarity with pre-existing trademarks. This study underscores the significance of judicial consistency in implementing the law and recommends measures to improve trademark protection in Indonesia.